Molecular and morphological surface analysis: effect of filling pastes and cleaning agents on root dentin - DAINEZI, Vanessa Benetello; IWAMOTO, Alexsandra Shizue; MARTIN, Airton Abrahão; SOARES, Luís Eduardo Silva; HOSOYA, Yumiko; PASCON, Fernanda Miori; PUPPIN-RONTANI, Regina Maria (Journal of Applied Oral Science, 2017)
The quality of the dentin root is the most important factor for restoration resin sealing and drives the outcome of endodontic treatment. Objective This study evaluated the effect of different filling pastes and cleaning agents on the root dentin of primary teeth using Fourier-transformed Raman spectroscopy (FT-Raman), micro energy-dispersive X-ray fluorescence (µ-EDXRF) and scanning electron microscopic (SEM) analysis. Material and Methods Eighty roots of primary teeth were endodontically prepared and distributed into 4 groups and filled according to the following filling pastes: Control-no filling (CP), Calen®+zinc oxide (CZ), Calcipex II® (CII), Vitapex® (V). After seven days, filling paste groups were distributed to 4 subgroups according to cleaning agents (n=5): Control-no cleaning (C), Ethanol (E), Tergenform® (T), 35% Phosphoric acid (PA). Then, the roots were sectioned and the dentin root sections were internally evaluated by FT-Raman, µ-EDXRF and SEM. Data was submitted to two-way ANOVA and Tukey tests (α=0.05). Results Regarding filling pastes, there was no significant difference in organic content. CP provided the lowest calcium values and, calcium/phosphoric ratio (Ca/P), and the highest phosphoric values. For cleaning agents there was no difference in organic content when compared to the C; however, T showed significantly higher calcium and Ca/P than PA. All groups showed similar results for phosphorus. The dentin smear layer was present after use of the cleaning agents, except PA. Conclusion The filling pastes changed the inorganic content, however they did not change the organic content. Cleaning agents did not alter the inorganic and organic content. PA cleaned and opened dentin tubules.